THE EFFECT OF SALES PROMOTION INTENSITY AND CELEBRITY ENDORSEMENT CONTENT EXPOSURE ON IMPULSIVE PURCHASE OF Z GENERATION to SOMETHINC LOCAL SKINCARE (SURVEY OF YOUTH AGED 19-24 YEARS AT JABODETABEK REGION) - Nabilah Amarilys; Djoko Setyabudi; Primada Qurrota Ayun (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2022)
SomeThinc known as the local skincare targeting user at young ages specifically gen z, having targets to achieved the 1st local cosmetic in rank and reach predicate as the most popular local skincare line. However, recently, real data by research shows that Somethinc still occupies the number 3 position with a revenue sales figure of 8.1 billion. The data proves that Somethinc is not categorized as leading local skincare brand in Indonesia and is still far from reaching its goals as a brand that can achieve Go Global conditions. Some of the steps taken by SomeThinc are discount promotions through social media and the use of celebrity endorsers in promoting their skincare products to increase its revenue. The study aims to determine the effect of sales promotion intensity, celebrity endorser content exposure on adolescent impulsive buying behaviour. The theory used in this research is Stimulus-Organism-Response theory and social cognitive theory. To determine the sample, researcher uses non-probability sampling technique. The samples studied were 100 people with female gender, aged 18-24 years, actively shopping for skincare products with minimum 3 times purchasing Somethinc skincare, have a monthly income and domiciled at Jabodetabek. The method used in this study is multiple linear regression analysis using primary data retrieved from questionnaire. The results showed that sales promotion intensity have influence over impulsive buying with a significant significance of 0.000. Furthermore, there is an influence between celebrity endorsement content exposure on impulsive buying with has a significant value of 0.000. In conclusion, there is an influence between sales promotion intensity, celebrity endorsement content exposure simultaneously has a significant effect on the impulsive buying variable by generation Z. Independent variable influenced dependent variables by 68,8% while 31.2% left affected by other variables outside the study.